Penerapan Metode Edutainment dalam Meningkatkan Kecerdasan Interpersonal Anak Usia 5- 6 Tahun di TKIT Darul Qur’an Madani Kota Parepare - Astiara Amaliasari; Tri Ayu Lestari Natsir; Syarifah Halifah; Tien Asmara Palintan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to improve the interpersonal intelligence of children aged 5–6 years through the implementation of the edutainment method at TKIT Darul Qur’an Madani, Parepare. The research employed Classroom Action Research (CAR) with Kurt Lewin’s model, conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 14 children from group B who initially showed low social interaction, cooperation, and empathy with peers. Data were collected through observation, interviews, documentation, and anecdotal notes, then analyzed descriptively using qualitative and quantitative approaches. The findings revealed a significant improvement in children’s interpersonal intelligence. In the first cycle, most children were categorized as Beginning to Develop and Developing as Expected. However, in the second cycle, through edutainment activities based on role playing with professional themes, 85% of the children achieved the Very Well Developed category. These results indicate that the edutainment method is effective in creating enjoyable, interactive, and meaningful learning experiences, which encourage children to communicate, collaborate, understand emotions, and develop empathy.